Effect of Addition of Activated Carbon on Lycopene Production of Blakeslea trispora in Submerge Cultivation - Li, Ye; Liu, Shu-Hui; Wang, Xiaojie (Asian Journal of Chemistry, 2014)
Lycopene production was increased when fine solid particle, activated carbon, was added to cultures of Blakeslea trispora (B. trispora) because of the enhanced dissolved oxygen concentrations. With 1 % (w/v) activated carbon added in the medium at zero day, lycopene production was 79 % higher than that of the control and the highest lycopene was 799 mg/L.